Impacto das nanopartículas de Sílica na transição de polímeros termossensíveis usados na administração controlada de medicamentos - Ribeiro, Lucas da Silva (2024)
Conventional systemic drug delivery methods have shown reduced effectiveness compared to localized release systems. Therefore, thermosensitive nanocomposites were synthesized using poly(N-vinylcaprolactam) (PNVCL) and silica nanoparticles for controlled and localized release of both hydrophilic (doxorubicin hydrochloride - DOX) and hydrophobic (naringin) drugs. The nanospheres were produced in two distinct sizes (80 and 330 nm), and their surfaces were modified with organosilane MPS to enable binding to the polymer. Although the inclusion of silica did not impact the sol-gel transition temperature of PNVCL, it induced changes in the transition profile, resulting in a diffuse transition due to reduced solvation of the polymeric chains. Additionally, there was a reduction in the transition enthalpy, attributed to the formation of smaller cooperative units resulting from the crosslinking role of the nanoparticles. Controlled release experiments demonstrated that all materials effectively regulated the release of the drugs over seven days at physiological temperature and under acidic and neutral pH conditions. The higher release under acidic conditions was attributed to increased erosion of the polymeric matrix. On the other hand, the lower release of naringin under physiological conditions was attributed to enhanced interaction with the hydrophobic interior of the polymer after the transition. Finally, cytotoxicity tests were conducted on pure or DOX-loaded polymers using non-tumor cells (L929) and bladder carcinoma tumor cells (MB49). The unloaded polymers showed no decrease in viability in any cell line after 24 hours, confirming the biocompatibility of the materials. However, the loaded polymers demonstrated cytotoxicity specifically when applied to tumor cells, with a synergistic effect between the 330 nm nanoparticles and the drug, resulting in an 80% reduction in viability in just 24 hours.